A study of dissimilar welding between mild steel and stainless steel on hardness and tensile shear test for gas tungsten arc welding (GTAW) - Ahmad Safwan Salim
This final year report is about the experimental study on the effects of the dissimilar weld joint design, edge preparation and joint dimension on the weldability of Gas Tungsten Arc Welding ( GTAW ) between mild steel and stainless steel. The analysis that has been used in this experimental is hardness Vickers test and tensile shear test to determine the hardenability and strengthened of the welding joint.